2020
DOI: 10.21873/anticanres.13993
|View full text |Cite
|
Sign up to set email alerts
|

APELA/ELA32 Reduces Iodixanol-induced Apoptosis, Inflammatory Response and Mitochondrial and DNA Damage in Renal Tubular Epithelial Cells

Abstract: Background/Aim: Contrast-induced AKI (CI-AKI) is an important clinical complication of intravascular use of iodinated contrast agents. The aim of the present study was to investigate the renoprotective effect of Apela on contrastinduced acute kidney injury. Materials and Methods: Blood samples from patients exposed to iodinated contrast agent were collected to assay for Apela and creatinine levels. The effects of ELA32 (Apela 32) on iodixanol-induced apoptosis, inflammation response, mitochondrial ROS producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These results suggested that iopromide-induced HEK 293 apoptosis is mediated through the induction of autophagy Iopromide elicited ROS production and suppressed the AKT signaling pathway. A previous study demonstrated that ROS production was induced by iodinated contrast media (40). Indeed, treatment of HEK 293 cells with 50 mgI/ml iopromide resulted in a 165% increase in ROS production (Figure 9A and B).…”
Section: Iopromide Triggers Autophagy To Protect Cells From Apoptosismentioning
confidence: 63%
“…These results suggested that iopromide-induced HEK 293 apoptosis is mediated through the induction of autophagy Iopromide elicited ROS production and suppressed the AKT signaling pathway. A previous study demonstrated that ROS production was induced by iodinated contrast media (40). Indeed, treatment of HEK 293 cells with 50 mgI/ml iopromide resulted in a 165% increase in ROS production (Figure 9A and B).…”
Section: Iopromide Triggers Autophagy To Protect Cells From Apoptosismentioning
confidence: 63%
“…Attempts to identify the endogenous levels of these peptides proved difficult owing to their physicochemical properties, which predispose ELA peptides to oxidation and poor chromatographic peaks. Given the beneficial effects of ELA signalling in various disease states including renal [ 9 , 37 , 38 , 8 , 32 , 33 ] and cardiovascular diseases [ 6 , 39 ], the long half-life observed here may suggest that ELA peptides could be a potential therapeutic option for managing these conditions.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we focused on the specific group of CKD patients, specifically at stages 3 and 4, who received only iodixanol as a contrast media. Previous studies in rats and in renal tubular epithelial cells reported that iodixanol caused mitochondrial dysfunction 19,20 . However, the roles of mitochondria in CI‐AKI in CKD patients are still unknown.…”
Section: Discussionmentioning
confidence: 99%